Modeling evolution of resistance by Maruca vitrata (Lepidoptera: Crambidae) to transgenic insecticidal cowpea in Africa - Onstad, D.W.; Kang, J.; Ba, Malick N.; Tamo, Manuele; Jackai, L.E.N.; Dabiré, C.; Pittendrigh, Barry Robert (Oxford University Press, 2012)
Wecreated a detailed model of the Maruca vitrata (F.) and cowpea [Vigna unguiculata (L.) Walp] system to study the possible evolution of resistance by the insect to transgenic insecticidal cowpea, which is under development. We focused on population dynamics and genetics in a region of west Africa. We simulated single-toxin and pyramided (two-toxin) cowpea and emphasized conservative, worst-case scenarios in our analysis. The results indicate that as long as a pyramided, transgenic cowpea can be developed, seed saving by farmers and reliance on natural refuge are not major problems for resistance management. Furthermore, it is possible that one or both toxins in the pyramid may not need to be high dose for evolution to be delayed signiÞcantly ( 20 yr or 80 generations for resistance to become a concern if transgenic cowpea is deployed in areas where M. vitrata is endemic). If efforts are made to deploy transgenic cowpea only into the regions where M. vitrata is not endemic, then there is little to no concern with resistance emerging in the M. vitrata population.